Aplikasi AHP Dalam Pengambilan Keputusan Pada Seleksi Karyawan - Purwatiningsih, Dyah Retno (Jurnal Teknik Industri, 2007)
PT. Hume Sakti Indonesia represent one of the company which experiencing of the problem of worker selection specially part of administration staff. Worker Selection in the year 2005 and work during more or less 1 year have less good performance. Existence of choices and criterions in election of employees, company should be able to take more accurate and precise decision. Also some alternative election of administration staff employees having equality in criterion which have been determined, so that make problems progressively complex. Beside that the existence of the condition of claiming decision making of employees selection which do not only can be answered yes or do not and also the existence of opinion of subjective in company. Method of Analytical Hierarchy Process (AHP) and of Fuzzy AHP tried for application to assist company in election of employees. Both method, hence will be got by consistency value of ratio, priority wight and best employees candidate with highest peringkat. At method of AHP employees owning rangking 2 highest by successively are Sulaiman 25.2% and Indrawati 22.4% while with method of Fuzzy AHP is Indrawati 26.5% and Sulaiman 22.8%. Both the method assign value differently, but method of Fuzzy AHP give result of more accurate because assessment to an criterion given in an value tolerance.